(untitled) (Health Renaissance, 2014)
Background: Ciliary body melanoma rarely grows transclerally by direct extension and can metastasize locally into the orbit or conjunctiva. Objective: To report a case of ciliary body melanoma presenting clinically as a mass in the lacrimal gland region. Case: A 40-year-old female presented to the ophthalmic out-patient department with the complaint of a swelling in the right upper and outer lid region for 4 years. Ocular examination revealed a phthisical right eye. A firm, non-tender mass was palpable in the temporal quadrant of the right supraorbital region. Ultrasonography showed retinal detachment of the right eye. The CT-scan of the orbit was reportedly suggestive of a right lacrimal gland mass. Superolateral transperiosteal orbitotomy was planned for excision of the lacrimal gland mass. Intraoperatively, a well defined mass arising from the supero-temporal region of the right globe was noticed. The procedure was converted to enucleation of the right eye. Histopathological examination of the mass showed features of ciliary body melanoma. Conclusion: Extrascleral extension of ciliary body melanoma can present as a mass in the lacrimal gland region. DOI: http://dx.doi.org/10.3126/hren.v11i3.9657 Health Renaissance 2013;11(3):287-289